Strategi Reading Aloud sebagai solusi meningkatkan keterampilan menghafal Dalil naqli pada Mata Pelajaran Fikih - Harahap, Oloan (MAN 4 Kota Pekanbaru, 2023)
This study aimed to improve the ability to memorize Naqli verses through the Reading Aloud strategy in MAN 4 Kota Pekanbaru students. The study used the classroom action research method in two cycles with 40 participants. The results showed a significant improvement in the ability of students to memorize Naqli verses after implementing the Reading Aloud strategy. In cycle I, the average score of students increased from 60.1 to 70.2, and in cycle II, the average score increased further to 80.8. These findings suggest that the Reading Aloud strategy effectively improves students' ability to memorize Naqli verses. Therefore, it is recommended that teachers use the Reading Aloud strategy in teaching the memorization of Naqli verses in the classroom. Further research can be conducted to test the effectiveness of the Reading Aloud strategy on a larger group of participants and involve more factors that affect the ability of students to memorize Naqli verses.